Communications networks simulated [Software Reviews] - Cruz, Rene L. (IEEE spectrum, 1999)
Opnet Modeler equips users with a graphical environment for creating, executing, and analyzing event-driven simulations of communication networks. This convenient software has many applications, typically communication protocol development and testing, analysis of protocol interactions, and network optimization and planning. Automated generation of common network topologies—rings, stars, random meshes— is also supported, backed up by utilities for importing network topologies in different formats. Pseudo-random traffic patterns can be automatically generated from algorithms specified by the user, or else real-world traffic traces may be imported from specific vendor formats. Several editor environments are provided, one for each object type. The objects are organized hierarchically—network objects (models) are linked collections of node and link objects, while node objects are linked collections of such objects as queue modules, processor modules, transmitters, and receivers. A radio version of the software includes radio transmitter antennas and receiver antennas, as well as support for moving node objects (including satellites). The basic unit of communication between processes is a data structure called a packet. Packet formats may be defined— that is, they may specify which fields may hold such standard data types as integers, floating-point numbers, and pointers to packets (this last capability enables the modeling of packet encapsulation). A data structure called an interface control information (ICI) can be shared between two instances of process models—yet another mechanism for interprocess communication and one that is especially convenient for modeling commands and replies in layered protocol architectures. A process may also dynamically spawn offspring processes, which can simplify the behavioral specification of such systems as servers. Several base process models accompany the package, modeling popular networking protocols and algorithms like border gateway protocol (BGP), transmissioncontrol protocol/Internet protocol (TCP/ IP), frame relay, Ethernet, asynchronous transfer mode (ATM), and weighted fair queuing (WFQ). The base models are useful for quick development of complex simulation models for common network architectures. They are also useful in an educational environment to concretely specify protocol behavior to students. Network, node, and process models can also be annotated with comments and graphics, in support of hypertext-like documentation. Complete on-line pdf-based documentation is provided. The tutorial manual uses simple examples to quickly teach the reader how to use this remarkably flexible product.